A silver(I) coordination polymer luminescent thermometer. (January 2017) - He, Yuan-Chun; Xu, Na; Zheng, Xiaofeng; Yu, Yang; Ling, Baoping; You, Jinmao
Abstract: A novel coordination polymer, namely, [Ag0.5 (H2 O)][Ag1.5 (L)(H2 O)]·2H2 O (1 ) (H2 L = 4'-((2-carboxyphenoxy)methyl)biphenyl-2-carboxylic acid) has been successfully synthesized at room temperature. In compound1, L anions bridge Ag(I) cations to form a one dimensional (1D) double chain structure, while there is an infinite Ag(I) chain joined by argentophilic interaction. Neighboring double chains are further extend into two dimensional (2D) supramolecular layers via intermolecular hydrogen-bonding interactions. Compound1 has been characterized by infrared spectrum (IR), elemental analysis and powder X-ray diffraction (PXRD) analysis, and the luminescent properties of1 were measured in detail. The luminescent intensity decreases regularly along with temperature increasing, which displays that compound1 is a potential luminescent thermometer. Graphical abstract: In this work, we report a novel silver(I) coordination polymer [Ag0.5 (H2 O)][Ag1.5 (L)(H2 O)]·2H2 O and its utilization as a luminescent thermometer. Highlights: Compound1 displays a two dimensional (2D) supramolecular layer. The luminescent properties of1 have been studied in detail. Compound1 is a potential luminescent thermometer.